Joint mobilization techniques for managing restricted range of motion - Harrelson, Gary; Leaver-Dunn, Deidre (Thorofare : SLACK Incorporated, 2002)
Joint mobilization: techniques for managing range of motion is a new and highly interactive CD-ROM designed to teach the core principles of joint mobilization at an introductory level in an environment that is user-friendly.
Systems requirements : Microsoft Windows and Apple Macintosh systems, Pentium-based PC or above, windows 95,98 or later, 6X CD-ROM drive, 32MB of RAM, 10MB or hard disk storage, 1 MB (or higher) SVGA video card, 8-bit sound blaster-compatible sound card, quicktime 5.0 or higher for windows, For macintosh: power pc, 32MB of RAM, 10MB of hard disk storage, Mac OS version 8.6 or later, quicktime 5.0 or higher for macointosh.
Keywords: Joints